Development of SATB based on LIEH shaped patch antenna for digital beamforming system - Islam, Mohammad Tariqul; Misran, Norbahiah; Yatim, Baharudin (2007)
This paper presents the design and development of the smart antenna system testbed (SATB). The SATB is developed based on using the novel L-probe fed inverted hybrid E-H (LIEH) microstrip patch element design arranged into 4 x 1 uniform linear array antenna. This paper reports the development of a software reconfigurable testbed for the implementation and evaluation of digital beamforming algorithm for smart antenna systems. The novel SATB developed based on modular design employing two novel designs of LIEH array antenna and software reconfigurable digital beamforming system (DBS). The modular concept of the system provides the capability to test the antenna hardware, beamforming unit, and beamforming algorithm in an independent manner, thus allowing the smart antenna system to be developed and tested in parallel, hence reduce the design time. The digital beamforming system was developed using a high performance TMS320C6711 (TM) floating-point DSP board and a 4-channel RF front-end receiver developed in-house. The over all peak side lobe level is achieved around at -10 dB for the different scanning angle. The antenna is used for a scan range as far as +/- 30 degrees.